Genealogi Tradisi Shalawat Nariyah di Desa Kroya - Achmad Fachrur Rozi (Asosiasi Sosiologi Agama Indonesia (ASAGI), 2020)
This article discusses the living of hadith, namely the study of the phenomena of practice or ritual originating from hadith. The tradition of Shalawat Nariyah which is one of the popular prayers that has taken root in Indonesian society. In Kroya Village, the Shalawat Nariyah Tradition is held every Wednesday night with 4444 congregations. The congregation is spread throughout the Kroya village mosque and takes turns every week. They believe that reading Shalawat Nariyah is able to facilitate sustenance. As generally the Shalawat Nariyah Tradition in some places is held on Friday nights, this is in line with the recommendations of the Prophet's hadith. But in Kroya, the tradition of reciting Shalawat Nariyah is held every Wednesday night.